Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar dan Aktivitas Belajar Siswa - Masitoh Fitriyanti; Lusiana Lulsiana; Ali Kameni (Journal of Elementary School (JOES), 2022)
This study aims to improve student learning outcomes and learning activities by applying problem-based learning model Problem Based Learning in mathematics subjects for students of class XI IPA 4 SMA Negeri 3 Lubuklinggau. This research uses a“classroom action research design that uses a classroom action research design using a qualitative approach using the Hopkins model in two cycles. Each cycle consists of four stages, namely planning, activity, observation, and reflection. The research subjects were 20 students of class XI”IPA 4 as many as 20 people. The object of the research is the results and learning activities. Data collection techniques were carried out through tests and student activity observation sheets. The results of the research in cycle 1, the average value reached 74.25 and the percentage of classical learning complete was 65%. In cycle II the average value increased to 85.5 and the presentation of classical learning was 90% complete. Student activity in learning cycle 1 with an average of 14.9 is included in the good category with a vulnerable value of 24 and a classical presentation of 62.1 (good enough), and increased in cycle II to 20.71 included in the very good category with a vulnerable value of 24, and classical presentation 81.05 (very good). Problem-based learning model Problem Based Learning (PBL) can improve learning outcomes and student learning activities in learning mathematics in class XI IPA 4 SMA Negeri 3 Lubuklinggau. Keywords: Learning Outcomes, Learning Activities, Problem Based Learning